REMOVAL OF NICKEL IONS BY Scenedesmus quadricauda FROM CONTAMINATED WATER UNDER LABORATORY CONDITIONS - Al-Mayaly, ITHAR (Iraqi Journal of Science, 2024)
The algal species Secenedesmus quadricauda was used to remove nickel ions from contaminated water (under laboratory conditions). It was exposed to different concentrations of nickel (2, 4, 6 and 8) ppm in order to measure it capacity to remove and tolerate this metal.The results showed that the alga was able to remove this metal with percentages of98, 53.5, 55.33 and 43% for the concentrations 2, 4, 6 and 8 ppm, respectively, inthe eighth days of the experiment period, while this ability was decreased in thefourteen days of the experiment period to: 80, 43.25, 36.83 and 26.62 % for theconcentrations 2, 4, 6, and 8, ppm respectively, as a result of death for some algalcells. So, it was concluded that this alga can tolerate nickel till 6 ppm, because it canremove more than 50 % from its concentration till the eighth day of the experimentperiod (8 days represents the life cycle of the studied alga according to some relatedreferences and most of the studies which used the same alga). This means that thealgal cells of this species can tolerate and live till the end of the life cycle with the6ppm of nickel (this concentration-6ppm- usually exceed the acceptable values ofnickel in water -0.05ppm- according to Iraqi rivers protection system.No.25\1967).